Pengaruh Penggunaan Cakram Diet Rendah Kalori terhadap Pengetahuan Gizi Pegawai Kantor Direktorat Jenderal Pajak - Karuniati, Annisa Fadhila; Yuliana, Indah; Arinda, Ditia Fitri; Sari, Desri Maulina (Puslitbang Sinergis Asa Professional, 2025)
The global prevalence of obesity has doubled over the past four decades, regardless of sex, age, ethnicity, or socioeconomic status. A low-calorie diet is an effective weight loss strategy for individuals who are overweight or obese. This study aimed to examine the effect of using a low-calorie diet disc on changes in nutrition knowledge among employees at the Head Office of the Directorate General of Taxes. A quasi-experimental design with a pre- and post-test control group was employed. The sample consisted of 100 employees, divided into a treatment group (n=50) who received a lecture using the diet disc as a medium, and a control group (n=50) who received education using PowerPoint slides. Data were analyzed using the Wilcoxon rank test followed by the Mann–Whitney U test. The results showed a significant difference in nutrition knowledge scores before and after the intervention in both groups (p<0.05), as well as a significant difference between the intervention and control groups (p<0.05), with an average increase of 35.4 points in the intervention group and 27.7 points in the control group, resulting in a final difference of 9.5 points between the groups. This study recommends that the Head Office of the Directorate General of Taxes conduct regular weekly low-calorie diet education sessions led by community nutritionists specializing in promotive and preventive health, to promote healthier and higher-quality staff.